The girls’anger . Thoughts on turning anger into clarity - Landa Etxebeste, Mariasun (Ondina - Ondine, 2020)
Stemming from the desire to support a non-sexist literature for children and young adults, the author wonders about the way in which one´s creativity and freedom can be combined with good intentions, a certain degree of protectionism, and even some level of censorship, which has been imposed on this topic by political correctness. Whether a gender sensitive literature can be produced in a society that is still sexist, without creating a gap between reality and fiction. She also reminds us, referring to three benchmarking woman authors (Simone de Beauvoir, Virginia Woolf y Astrid Lindgren), that authors should write from their own personal imaginary and creative freedom. Authors may not give them up because literature conveys their need of self-awareness/self-knowledge, expression and communication. Key words: non-sexist literature, outrage, political correctness, lucidity, creative freedom.